(untitled) (Iranian Journal of Kidney Diseases, 2024)
IgG4-related disease (IgG4-RD) is a chronic systemic inflammatory disease, characterized by tissue infiltration of lymphocytes and IgG4-secreting plasma cells, presenting by fibrosis of different tissues, which is usually responsive only to oral steroids therapy. Kidneys are the most commonly involved organs, exhibiting renal insufficiency, tubulointerstitial nephritis, and glomerulonephritis. Here, we describe a patient with acute renal insufficiency who was presented with edema, weakness, anemia and multiple lymphadenopathies. Kidney and lymph node biopsy showed crescentic glomerulonephritis in kidneys and lymphoplasmacytic infiltration in lymph nodes. After a course of treatment with an intravenous pulse of corticosteroid and cyclophosphamide, the patient’s symptoms subsided, and kidney function improved. DOI: 10.52547/ijkd.7788